KEMISKINAN DAN ADAPTASI MASYARAKAT NELAYAN PADA EKOSISTEM DAERAH ALIRAN SUNGAI LEMPUING, SUMATERA SELATAN : Suatu Pembedahan Fenomena Sosial Menggunakan Perspektif Ekologi - Nasution, Zahri (Jurnal Masyarakat dan Budaya, 2005)
Fishermen society as a social system and Lempuing river basin ecosystem as an ecological system has been interacting and influencing each other. They interaction were producing a fishermen society poverty phennomena. Negative impacts on river basin ecosystem has been influencing fisheries activities. These impacts on river basin ecosystem namely loss energy and material sources were occuring. Than, prosperity of the fishermen society were decrease. In this case, selection and adaption concept of Rambo is useful to used in order to explanation that phennomena. Energy and material input from social system and other wise, any changes on social system or ecological system are discussion in this paper. At the end, the fishermen poverty, they adaptation, fish species tolerances to the Lempuing river basin ecosystem are also disscussed.